Rainbow Vertex Connection Number pada Keluarga Graf Roda - Firman Firman; Dafik Dafik; Ermita Rizki Albirri (jcgant, 2022)
The rainbow vertex connection was first introduced by krivelevich and yuster in 2009 which is an extension of the rainbow connection. Let graph G =(V,E) is a connected graph. Rainbow vertex-connection is the assignment of color to the vertices of a graph G, if every vertex on graph G is connected by a path that has interior vertices with different colors. The minimum number of colors from the rainbow vertex coloring in graph G is called rainbow vertex connection number which is denoted rvc(G). The result of the research are the rainbow vertex connection number of family wheel graphs.